3D seismic analysis of the structure and evolution of a salt-influenced normal fault zone: a test of competing fault growth models - Jackson,CAL; Rotevatn,A (Journal of Structural Geology, 2013)
In this paper we determine the structure and evolution of a normal fault system by applying qualitative and quantitative fault analysis techniques to a 3D seismic reflection dataset from the Suez Rift, Egypt. Our analysis indicates that the October Fault Zone is composed of two fault systems that are locally decoupled across an salt-bearing interval of Late Miocene (Messinian) age. The sub-salt system offsets pre-rift crystalline basement, and was active during the Late Oligocene-early Middle Miocene. It is composed of four, planar, NW-SE-striking segments that are hard-linked by N-S-striking segments, and up to 2 km of displacement occurs at top basement, suggesting that this fault system nucleated at or, more likely, below this structural level. The supra-salt system was active during the Pliocene-Holocene, and is composed of four, NW-SE-striking, listric fault segments, which are soft-linked by unbreached relay zones. Segments in the supra-salt fault system nucleated within Pliocene strata and have maximum throws of up to 482 m. Locally, the segments of the supra-salt fault system breach the Messinian salt to hard-link downwards with the underlying, sub-salt fault system, thus forming the upper part of a fault zone composed of: (i) a single, amalgamated fault system below the salt and (ii) a fault system composed of multiple soft-linked segments above the salt. Analysis of throw-distance (T-x) and throw-depth (T-z) plots for the supra-salt fault system, isopach maps of the associated growth strata and backstripping of intervening relay zones indicates that these faults rapidly established their lengths during the early stages of their slip history. The fault tips were then effectively ‘pinned’ and the faults accumulated displacement via predominantly downward propagation. We interpret that the October Fault Zone had the following evolutionary trend; (i) growth of the sub-salt fault system during the Oligocene-to-early Middle Miocene; (ii) cessation of